2004
DOI: 10.1073/pnas.0308701101
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of thioredoxin-targeted proteins in Escherichia coli

Abstract: Thioredoxin, a ubiquitous and evolutionarily conserved protein, modulates the structure and activity of proteins involved in a spectrum of processes, such as gene expression, apoptosis, and the oxidative stress response. Here, we present a comprehensive analysis of the thioredoxin-linked Escherichia coli proteome by using tandem affinity purification and nanospray microcapillary tandem mass spectrometry. We have identified a total of 80 proteins associated with thioredoxin, implicating the involvement of thior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
168
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(178 citation statements)
references
References 52 publications
(42 reference statements)
3
168
1
2
Order By: Relevance
“…EF-G in spinach chloroplasts (28) and E. coli (29) and EF-2 in Arabidopsis thaliana (30) and Chlamydomonas reinhardtii (31) were identified as candidates for targets of thioredoxin, as was EF-G (Slr1463) in Synechocystis (32). In the present study, we demonstrated for the first time, to our knowledge, that EF-G is an actual and functional target of thioredoxin.…”
Section: Oxidation Of Two Specific Cysteine Residues Inactivates Ef-g-mentioning
confidence: 63%
See 1 more Smart Citation
“…EF-G in spinach chloroplasts (28) and E. coli (29) and EF-2 in Arabidopsis thaliana (30) and Chlamydomonas reinhardtii (31) were identified as candidates for targets of thioredoxin, as was EF-G (Slr1463) in Synechocystis (32). In the present study, we demonstrated for the first time, to our knowledge, that EF-G is an actual and functional target of thioredoxin.…”
Section: Oxidation Of Two Specific Cysteine Residues Inactivates Ef-g-mentioning
confidence: 63%
“…Thioredoxin affinity chromatography captured a number of putative targets of thioredoxin (25)(26)(27)(28)(29)(30)(31)(32). EF-G in spinach chloroplasts (28) and E. coli (29) and EF-2 in Arabidopsis thaliana (30) and Chlamydomonas reinhardtii (31) were identified as candidates for targets of thioredoxin, as was EF-G (Slr1463) in Synechocystis (32).…”
Section: Oxidation Of Two Specific Cysteine Residues Inactivates Ef-g-mentioning
confidence: 99%
“…Comparison of ICAT and iTRAQ Analysis Results-The importance of Trx1 has spurred enormous interest in identifying its targets, an endeavor that has been aided by the developments of innovative techniques such as fluorescent diagonal electrophoresis (5) and affinity chromatography (28,29). However, these approaches have not been able to provide quantitative information regarding the degree or the specific sites of reduction; both are critical for relating protein redox status and the associated biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous proteomic surveys have documented the specificity of Trx in target recognition (13)(14)(15). However, the molecular mechanism underlying this process, particularly in the absence of a signature Trx-binding sequence or structural motif, has remained largely unknown.…”
mentioning
confidence: 99%